Injectable photocrosslinking spherical hydrogel-encapsulated targeting peptide-modified engineered exosomes for osteoarthritis therapy - Junlai Wan; Zhiyi He; Renpeng Peng; Xiaopei Wu; Ziqing Zhu; Jiarui Cui; Xiaoxia Hao; Anmin Chen; Jiaming Zhang; Peng Cheng (Journal of Nanobiotechnology, 2023)
Abstract Osteoarthritis (OA) is a common degenerative joint disease urgently needing effective treatments. Bone marrow mesenchymal stromal cell-derived exosomes (Exo) are considered good drug carriers whereas they have limitations such as fast clearance and low retention. This study aimed to overcome the limitations of Exo in drug delivery using multiple strategies. Novel photocrosslinking spherical gelatin methacryloyl hydrogel (GelMA)-encapsulated cartilage affinity WYRGRL (W) peptide-modified engineered Exo were developed for OA treatment and the performance of the engineered Exo (W-Exo@GelMA) loaded with a small inhibitor LRRK2-IN-1 (W-Exo-L@GelMA) was investigated in vitro and in vivo. The W-Exo-L@GelMA showed an effective targeting effect on chondrocytes and a pronounced action on suppressing catabolism and promoting anabolism in vitro. Moreover, W-Exo-L@GelMA remarkably inhibited OA-related inflammation and immune gene expression, rescuing the IL-1β-induced transcriptomic responses. With enhanced retention in the joint, W-Exo-L@GelMA demonstrated superior anti-OA activity and cartilage repair ability in the OA murine model. The therapeutic effect was validated in the cultured human OA cartilage. In conclusion, photocrosslinking spherical hydrogel-encapsulated targeting peptide-modified engineered Exo exhibit notable potential in OA therapy. Engineering Exo by a series of strategies enhanced the targeting ability and retention and cartilage-targeting and Exo-mediated drug delivery may offer a novel strategy for OA treatment. Clinical trial registration: Not applciable. Graphical Abstract